THE THERAPEUTIC POWER OF DIGITAL READING: ENHANCING MENTAL HEALTH IN PSYCHIATRIC SETTINGS - Vlachou, Sofia Katerina; Papadakis, Nikos Georgios (International Research Journal Diagnostics, 2024)
Bibliotherapy has long been recognized as a therapeutic approach to promoting mental health. With the advent of digital technology, a new form known as 'digital bibliotherapy' has emerged. This innovative approach involves delivering therapeutic content through electronic devices, such as computers, tablets, and smartphones, offering a blend of the therapeutic benefits of bibliotherapy with the convenience and accessibility of digital technology. Digital bibliotherapy integrates interactive elements and multimedia resources, creating a personalized and immersive therapeutic experience. Notably, this approach addresses issues of accessibility and inclusivity by overcoming geographical and temporal limitations and reaching a more diverse audience. It proves particularly advantageous for individuals facing obstacles to traditional therapy, whether due to geographical remoteness, stigma, or financial concerns.